The potential application of probiotics and prebiotics for the prevention and treatment of COVID-19 (2020)
COVID-19 is a pandemic disease caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This new viral infection was first identified in China in December 2019, and it has subsequently spread globally. The lack of a vaccine or curative treatment for COVID-19 necessitates a focus on other strategies to prevent and treat the infection. Probiotics consist of single or mixed cultures of live microorganisms that can beneficially affect the host by maintaining the intestinal or lung microbiota that play a major role in human health. At present, good scientific evidence exists to support the ability of probiotics to boost human immunity, thereby preventing colonization by pathogens and reducing the incidence and severity of infections. Herein, we present clinical studies of the use of probiotic supplementation to prevent or treat respiratory tract infections. These data lead to promising benefits of probiotics in reducing the risk of COVID-19. Further studies should be conducted to assess the ability of probiotics to combat COVID-19.